Integrated Education and Screening Program for Adolescents at Adolescent Community Based Integrated Post for Prevention and Early Detection of Hypertension - Sukmawati; Dian Kurniasari Yuwono; Nurarifah Nurarifah; Nitro Galenso; Dg Mangemba (Jurnal Pengabdian Masyarakat Lentora, 2026)
Hypertension can occur in adolescents and is often asymptomatic. However, adolescent participation in posyandu, one of whose goals is early detection of non-communicable diseases (NCDs), remains low. Purpose: This community service aims to promote health to adolescents at the adolescent posyandu in an effort to prevent and detect hypertension early. Methods: Early detection was conducted by measuring blood pressure, providing counseling, distributing leaflets, and administering pre-post tests. The activity was carried out at the adolescent posyandu in Awu Village on July 31, 2025, attended by 5 cadres and 15 adolescents. Results: All adolescent participants did not know their blood pressure. The blood pressure examination showed that one adolescent had above-normal blood pressure (140 mmHg). The pre-post test knowledge level increased by an average of 41%. Counseling proved to be an effective strategy to increase knowledge. Previously unknown information was that hypertension can occur in adolescents and is asymptomatic. The most effective way to detect it is to measure blood pressure regularly. Conclusion: The final evaluation showed that this community service activity was successful, as seen from the enthusiasm of the participants. It is hoped that adolescents will be empowered, have the knowledge, attitudes, and skills for healthy living, and help break the chain of hypertension.